PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS - Rista Farida; Angga Nuraufa Zamzami Saputra; Choirul Anwar (Comprehensive Journal of Islamic Studies, 2023)
This research aims to increase the motivation and social studies learning outcomes of class IV students in the Social Sciences (Social Sciences) subject at MI Plus Maarif NU Bacem, Ponggok District, Blitar Regency using the Role Playing method. This research is classroom action research (PTK) in 2 cycles. The instrument used in this research is a test to measure student learning outcomes. The results of the research show that: 1) The application of the method used is Role Playing, 2) Likewise, the results from cycle I to cycle II experienced an increase in learning outcomes.